IMPROVEMENT OF METHODS OF REHABILITATION OF THE ABDOMINAL CAVITY WITH DIFFUSE PURULENT PERITONITIS UNDER EXPERIMENTAL CONDITIONS - V. P. Budasheyev (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
This paper presents the results of experimental studies of intraoperative sanation of abdominal cavity at diffuse purulent peritonitis (in 25 dogs), compared with the results of readjustment of the abdominal cavity with diffuse purulent peritonitis (74 patients) using the universal domestic antiseptic "anolyte". The results of experimental and clinical studies show that presented method of readjustment of the abdominal cavity can be used in clinical practice.